Physical-hydrical characteristics of Yellow Latosol, Red-Yellow Podzolic, and Hydromorphic Podzolic soils in the Amazon State - Corrêa, J. C. (Pesquisa Agropecuaria Brasileira, 2014)
The soil physical and hydrological properties of a clayey yellow Latossol, a clayey Red-Yellow Podzolic, a loamy Red-Yellow Podzolic, and a Hydromorphic Podzol were evaluated in Manaus, AM, Brazil. The area is located on the left side of AM-010, highway 30 km from Manaus proceeding towards Itacoatiara. Aeration conditions are medium for the first three soils and good for the Hydromorphic Podzol. Soil water characteristic curves indicated that: a) soil moisture release was minimal at tensions greater than two atmospheres in the first three soils and one atmosphere for the latter soil; b) available soil water is medium for the first three soils and low for the latter soil.